A 3D Hierarchical Host with Enhanced Sodiophilicity Enabling Anode‐Free Sodium‐Metal Batteries (Adv. Mater. 14/2022). Issue 14 (7th April 2022) - Lee, Kyungbin; Lee, Young Jun; Lee, Michael J.; Han, Junghun; Lim, Jeonghoon; Ryu, Kun; Yoon, Hana; Kim, Byung‐Hyun; Kim, Bumjoon J.; Lee, Seung Woo
Abstract : Sodium‐Metal Batteries In article number 2109767, Byung‐Hyun Kim, Bumjoon J. Kim, Seung Woo Lee, and co‐workers report anode‐free sodium‐metal batteries. The cover image depicts two batteries: the left shows typical sodium‐metal batteries, where the continuous dendrite growth in the sodium‐metal anodes causes a short‐circuit, resulting in battery failure. Contrarily, the right shows highly reversible porous carbon hosts with carbon‐shell‐coated Fe nanoparticles for the sodium‐metal anode, allowing superior cycling performance and improving the energy density of the batteries.